High incidence and persistence of airborne allergen sensitization up to age 19 years. Issue 5 (28th October 2016) - Rönmark, E.; Warm, K.; Bjerg, A.; Backman, H.; Hedman, L.; Lundbäck, B.
Abstract: Background: Longitudinal population‐based studies about the natural history of allergic sensitization are rare. The aim was to study incidence and persistence of airborne allergen sensitization up to young adulthood and risk factors for early and late onset of sensitization. Methods: All children aged 7–8 years in two municipalities in Northern Sweden were invited to a parental questionnaire and skin prick tests (SPTs) to ten airborne allergens, and 2148 (88%) participated. The protocol was repeated at age 11–12 and 19 years, and 1516 participated in all three examinations. Results: Prevalence of any positive SPT increased from 20.6% at age 7–8 years to 30.6% at 11–12 years, and 42.1% at 19 years. Animals were the primary sensitizers at age 7–8 years, 16.3%, followed by pollen, 12.4%. Mite and mold sensitization was low. Mean annual incidence of any positive SPT varied between 2.8 and 3.4/100 per year, decreased by age for animal, and was stable for pollen. Sensitization before age 7–8 years was independently associated with family history of allergy, OR 2.1 (95% CI 1.6–2.8), urban living, OR 1.9 (95% CI 1.2–2.9), and male sex, OR 1.3 (95% CI 1.0–1.7), and negatively associated with birth order, OR 0.8 (95% CI 0.7–1.0), and furry animals at home, OR 0.7 (95% CI 0.7–0.9). Incidence after age 11–12 years was associated only with family history of allergy. Multisensitization at age 19 years was significantly associated with early age at sensitization. Remission of sensitization was uncommon. Conclusion: The increasing prevalence of allergic sensitization by age was explained by high incidence and persistence. After age 11–12 years, the factors urban living, number of siblings, and male sex lost their importance.